PERAN COMMUNITY BASED TOURISM DALAM PENGEMBANGAN CULTURAL TOURISM BERKESINAMBUNGAN - Santoso, Raymond Eka Putra (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
Community based cultural tourism is one of the efforts of local cultural developmentthrough the tourism sector, which not only presents the beauty, but also to contribute to theconservation of the environment, and society as a main controller in its development. Still hasmany problems, both from the environmental aspects, aspects of management, to aspects ofhuman resources, so undeveloped tourist activity. Therefore, we need a study to analyze thepotential of community-based ecotourism development to achieve these objectives, an analysison all aspects, namely the analysis of the object aspects and attractions, social aspects, aspectsof management, to aspects of the implementation of community empowerment. Required thecooperation of the various parties rather activities of local cultural development through tourismsector can work well and be sustainable for the future.Keyword : Community Based Tourism, Cultural Tourism, Community Development.